The Information Society as a Space of New Social Antinomies - Anvarovna, Mukhiddinova Shahnoza (Indonesian Journal Publisher, 2025)
This study examines the philosophical and sociocultural contradictions that emerge in the context of the information society. The purpose of the research is to analyze the antinomies of digital transformation, focusing on freedom and control, information accessibility and informational noise, virtual connectivity and social isolation, as well as the fluidity of identity in digital culture. The research is based on philosophical analysis, comparative review of theoretical literature, and synthesis of contemporary debates in the philosophy of technology and digital culture. The findings indicate that informatization creates both opportunities and risks. On the one hand, digital technologies expand access to knowledge, foster innovation, and democratize communication. On the other hand, they generate new challenges such as surveillance, deintellectualization, digital loneliness, fragmented identity, and environmental burdens of ICT. The study concludes that the information society represents a contradictory space in which progress and alienation coexist, making philosophical reflection and digital ethics essential for sustaining human dignity in the age of digital transformation.